Reniform Nematode Resistance in Selected Soybean Cultivars - Robbins, R. T. (Society of Nematologists, 1999)
Two hundred eighty-two soybean cultivars from the variety testing programs of Arkansas and Mississippi were tested in greenhouse pot experiments during summer 1998 to identify soybean cultivars with resistance to the reniform nematode, Rotylenchulus reniformis. Also included in the tests were the resistant cultivars Forrest and Hartwig, the susceptible control Braxton, and fallow infested soil, which were used as controls. Numbers of reniform nematode extracted from the soil and roots and the ratio of the numbers reproducing on each cultivar compared to the number reproducing on Forrest are reported. Cultivars with reproduction not significantly different from Forrest were classified resistant, whereas those with greater reproductive indices were considered susceptible. One of the 18 cultivars of relative maturity group (RMG) ≤4.4 was classified as resistant. For the 86 cultivars of RMG 4.5-4.9, 18 were found to be resistant. Of the 43 cultivars of RMG 5.0-5.4, 16 were resistant, while 43 of the 91 cultivars of RMG 5.5-5.9 were resistant. Fifteen of the cultivars with an RMG of ≥6.0 were classed as resistant. These data will be useful in the selection of soybean cultivars to use in rotation with cotton to help control the reniform nematode.